Financial Development, Institutions, Gender and Entrepreneurship in the United Arab Emirates - Hameli, Afra; Kampouris, Ilias; Machaal, Amal Kamal; Mertzanis, Charilaos (Asian Journal of Empirical Research, 2021)
The paper explores the role of financial development on entrepreneurship in the United Arab Emirates by using data on new business registration and new business density over the period 2006-2018. The country is undergoing a rapid transformation phase characterizzed by substantial efforts to boost private sector entepreneurship. The data is drawn from the World Bank’s World Development Indicators. We use the International Monetary Fund’s composite financial development index to capture financial development in the country. The index comprises information on financial depth, access and efficiency by both financial institutions and markets. The paper controls for the impact on the macroeconomic conditions, institutional factors, such as gender equality and the fear of failure, the innovation environment and the business startup environment. The results show that financial development is a robust predictor of entepreneurial activity in the UAE. Macroeconomic, institutional and innovation conditions further mediate the link in more or less significant ways.